Profil HIV/AIDS di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R.D. Kandou Manado Periode Januari 2009 sampai dengan Desember 2018 - Sumampouw, Yurissco B.; Rampengan, Novie H.; Mantik, Max F. J. (Universitas Sam Ratulangi, 2020)
Abstract: Human immunodeficiency virus (HIV) infection and acquired immunodpeficiency syndrome (AIDS) are health problems worldwide. Risk factors that are supposed to increase the incidence of HIV/AIDS include perinatal, homosexual, heterosexual, pattern of sexual relation, family with positive HIV/AIDS sufferers who do not use protective equipment, and injection drug users. This study was aimed to determine the profile of HIV/AIDS at the Department of Pediatrics Prof. Dr. R. D. Kandou Manado. This was a descriptive and retrospective study using data of Voluntary Counseling Test (VCT) from January 2009 to December 2018. The results showed that there were 75 patients, most were 13-18 years (32%) and male sex (50.67%). The most common transmission was perinatal transmission (68%). Stage III had the highest percentage (80%). First-line therapy was found as the most common (68%), albeit 23 patients (30.7%) had not received ARV therapy. There were 28 patients (37.33%) who lived with HIV/AIDS. In conclusion, the highest prevalence of HIV was in 2018 and the most common patients were male, aged 13-18 <18 years, and had perinatal transmission. and 28 children living with HIV. Some patients still lived with HIV/AIDS.Keywords: human immunodeficiency virus, acquired immunodeficiency syndromeÂ Abstrak: Infeksi human immunodeficiency virus (HIV) dan acquired immunodeficiency syndrome (AIDS) merupakan masalah kesehatan di dunia. Faktor-faktor risiko yang diperkirakan meningkatkan angka kejadian HIV/AIDS antara lain: perinatal, homoseksual, heteroseksual, pola hubungan seks, keluarga dengan pengidap HIV/AIDS positif yang tidak menggunakan pelindung, dan pemakai alat suntik. Penelitian ini bertujuan untuk mengetahui profil HIV-AIDS di Bagiaan Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou. Jenis penelitian ialah deskriptif retrospektif. Penelitian ini menggunakan data dari Voluntary Counseling Test (VCT) RSUP Prof. Dr. R.D. Kandou Manado selama Januari 2009-Desember 2018. Hasil penelitian mendapatkan 75 pasien dan yang terbanyak ialah usia 13-18 tahun (32%), dan jenis kelamin laki-laki (50,67%). Penularan terbanyak ialah perinatal (68%) Stadium terbanyak ialah stadium III (80%) dan terapi lini I yang terbanyak (68%) namun terdapat 23 pasien (30,7%) yang belum mendapatkan terapi ARV. Terdapat 28 pasien (37,33%) yang hidup dengan HIV/AIDS. Simpulan penelitian ini ialah prevalensi tertinggi HIV pada tahun 2018 dan pasien yang terbanyak berjenis kelamin laki-laki, usia 13-<18 tahun, dengan penularan perinatal. Sebagian pasien hidup dengan HIV/AIDS.Kata kunci: human immunodeficiency virus, acquired immunodeficiency syndrome